Characterization and Optimization of Alkaline Protease Production from Bacillus licheniformis HSW-16 Isolated from Sambhar Salt Lake - Singh, Rajnish Prakash; Jha, Prabhat Nath (International Journal of Applied Sciences and Biotechnology, 2015)
Halophilic microorganisms are recognized as potential source of secondary metabolites including enzymes and drugs with wide agricultural and industrial applications. In the present study protease producing halotolerant bacterium Bacillus licheniformis HSW-16 was isolated from hypersaline Sambhar lake, Rajasthan India. Protease production was performed by using azocasein as substrate. Confirmation of protease production was also done by amplification of alkaline protease gene and sequencing. The various nutritional factors such as carbon and nitrogen source and other physiological parameters like pH, temperature, incubation time and agitation speed were optimized for optimum protease production. The enzyme was active in pH range 7-10, temperature 25 °C-40 °C and salt concentration of 1.5M. The characteristics demonstrated by this isolate showed that it could be used as a potential source of enzyme. Int J Appl Sci Biotechnol, Vol 3(2): 347-351 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12757